C-Reactive Protein Serum Levels as an Internal Load Indicator of Sprints in Competitive Football Matches - Jatene, Pedro; dos Santos, Gustavo Silva; Portella, Daniel Leite (International Journal of Sports Medicine, 2019)
This study compared internal load variable dynamics across three consecutive football matches and investigated its relationship with the number of sprints performed by players. Twenty-three male players had blood and salivary samples collected for hormonal concentration (testosterone, cortisol, and testosterone-cortisol ratio), and serum analysis (interleukin-6, interleukin-1-beta, and c-reactive-protein), respectively. Sprints were measured through Global Position System devices. Testosterone and testosterone-cortisol-ratio presented a decreasing behavior up to the second match, and all other indicators presented an increasing behavior during the same period, c-reactive-protein was the only indicator observed to significantly rise up to the third match as well (0.38±0.02 mg/L; 0.49±0.05 mg/L; 0.69±0.05 mg/L; 0.89±0.08 mg/L). C-reactive-protein showed strong correlations with sprints in the second and third matches (p<0.01, r=0.71 and 0.79), and weak-to-moderate in the first one (p<0.05, r=0.59). Interleukin-6 and interleukin-1-beta presented weak-to-moderate correlation in every match (p<0.05, r=0.48 to 0.51; r=0.51 to 0.55) while testosterone-cortisol ratio presented weak-to-moderate correlation only in the third one (p<0.05, r=0.42). Multilevel linear regression showed that c-reactive-protein had a higher R2 than other biomarker in any regression model (R2=0.624; p<0.001). Therefore, c-reactive-protein can be a valid and reliable indicator of sprinting in competitive football. Future research should explore longer periods of monitoring and/or others external load variables so that other behaviors may arise to knowledge.
Keywords: athletes; workload; muscle damage; biomarkers